PERITONITIS BAKTERIAL SPONTAN DAN PENGARUH PENGHAMBAT POMPA PROTON PADA PENDERITIA SIROSIS HATI - Lelosutan, Syafruddin; Sakura Muhammad Tola; Intan Keumala Dewi; Endah Purnamasari; Diniwati Mukhtar; Muhammad Samsul Mustofa; Himmi Marsiati (Medika Alkhairaat: Jurnal Penelitian Kedokteran dan Kesehatan, 2024)
Abstract. Spontaneous bacterial peritonitis (SBP) is an acute infection of ascitic fluid in the abdominal cavity (ACAF - ascitic fluid that accumulates in the abdominal cavity) in patients with portal hypertension who experience ascites and is a serious complication of internal medical emergencies in patients with Liver cirrhosis (SH) and nephrotic syndrome (SN). A pathophysiological condition that may be contaminating, such as contamination of dialysate fluid in patients with chronic renal failure (CKD) who receive peritoneal dialysis (PD) or that stimulates the transmission of germs, such as long-term use of proton pump inhibitors (PPI) in SH sufferers, could be an infectious etiology. The pathophysiology of SBP in SH is an inoculation of bacteria in the form of intestinal organisms in ACAF which most likely (> 90%) comes from bacterial contamination due to transmission of germs from the gastrointestinal tract in the presence of enteric microorganism endotoxin which is a direct transmural migration (DTM) of hollow and solid organ bacteria. stomach (gastrointestinal system / esophago-gastro-duodenalis, small and large intestines and pancreatic-hepato-biliary system / pancreas, liver, gallbladder and its ducts); known as enteric bacterial translocation (EBT). Understanding the pathophysiological process of SBP is generally not paid much attention by clinical practitioners, let alone understanding what types of germs are in ascitic fluid. This can be seen from the rare critical assessment (culture and cytology) of the existing ascitic fluid, perhaps even thinking about the presence or absence of ascites at the start of a case of liver cirrhosis (SH). General results show that SH patients who receive PPI therapy appear to experience SBP more often than those who do not receive PPI therapy in their treatment. This review aims to be a critical review of the use of PPIs in liver cirrhosis sufferers to warn of the risk of germ migration from the gastrointestinal tract to ascitic fluid which might cause SBP. Study and understand the literature relating to the management of SBP and the risks of using PPIs in liver cirrhosis sufferers. Gain an understanding of the risks of using PPIs in liver cirrhosis sufferers.